Torsional fatigue strength of reciprocating and rotary pathfinding instruments manufactured from different NiTi alloys - Rodrigo Ricci VIVAN; Murilo Priori ALCALDE; George CANDEIRO; Giulio GAVINI; Celso Luis CALDEIRA; Marco Antonio Hungaro DUARTE (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract To evaluate the torsional properties of engine-driven pathfinding instruments manufactured from different NiTi alloys - R-Pilot (tip size 12.5;.04 taper; M-Wire) and One G (tip size 14;.03 taper; Conventional NiTi). A total of 40 NiTi instruments from engine-driven pathfinding instruments (n = 20) were used. The torsion tests followed ISO 3630-1 (1992). Three millimeters of each instrument tip was fastened to a small load cell by a lever arm linked to the axis of torsion. During the test, the torsion testing machine software measured the maximum torsional strength and angle of rotation (0) before instrument failure. The fractured surface of each instrument was assessed by scanning electron microscopy (SEM). In addition, a supplementary examination was performed to measure the cross-sectional area and the metal mass volume of each instrument 3 mm from the tip. Data were analyzed using a t-test, with significance level set at 5%. R-pilot had significantly higher torsional strength than did One G (p < 0.05). Regarding the angle of rotation to fracture, One G had higher angles than did R-Pilot (p < 0.05). The supplementary examination showed that R-Pilot had the highest cross-sectional area and volume of metal mass at 3 mm from the tip (p < 0.05). R-pilot (M-Wire NiTi alloy) had a significantly higher torsional strength and One-G (superelastic NiTi alloy) had the highest angle of rotation to fracture.